Analisi Tingkat Kecemasan Matematika Siswa SMA Terhadap Sudden Test Matematika Ditinjau dari Tingkat Kemampuan Matematika Siswa - Wibowo, Angga Setiawan Adi; Ismail, Ismail (MATHEdunesa, 2024)
Mathematics anxiety is a feeling of anxiety, tension, or fear that interferes with your ability to do mathematics and chooses to avoid situasions related to mathematics. Mathematics anxiety is experienced by students who are not good at mathematics or who are good at mathematics. Factors that make atudents experience mathematics anxiety include daily tests, class promotion exam, sudden test, and so on. The research conducted aims to desribe the level of high schol students mathematics anxiety towards sudden mathematics test in terms of the level of students mathematics ability. This research is a descriptive research with a qualitative approach. The subjects in this study were 3 students with different levels of mathematics ability. The research was conducted using instruments including mathematics test worksheets, and interview guidelines. The results of this study showed that students with high levels of mathematics ability experienced very low mathematics anxiety, students with moderate levels of mathematics ability experienced low mathematics anxiety, and students with low levels of mathematics ability experienced high mathematics anxiety.